Vasculogenic mimicry formation in EBV-associated epithelial malignancies. Issue 1 (December 2018) - Xiang, Tong; Lin, Yu-Xin; Ma, Wenlong; Zhang, Hao-Jiong; Chen, Ke-Ming; He, Gui-Ping; Zhang, Xiao; Xu, Miao; Feng, Qi-Sheng; Chen, Ming-Yuan; Zeng, Mu-Sheng; Zeng, Yi-Xin; et al.
Abstract Epstein-Barr virus (EBV)-associated epithelial cancers, including nasopharyngeal carcinoma (NPC) and approximately 10% of gastric cancers, termed EBVaGC, represent 80% of all EBV-related malignancies. However, the exact role of EBV in epithelial cancers remains elusive. Here, we report that EBV functions in vasculogenic mimicry (VM). Epithelial cancer cells infected with EBV develop tumor vascular networks that correlate with tumor growth, which is different from endothelial-derived angiogenic vessels and is VEGF-independent. Mechanistically, activation of the PI3K/AKT/mTOR/HIF-1α signaling cascade, which is partly mediated by LMP2A, is responsible for EBV-induced VM formation. Both xenografts and clinical samples of NPC and EBVaGC exhibit VM histologically, which are correlated with AKT and HIF-1α activation. Furthermore, although anti-VEGF monotherapy shows limited effects, potent synergistic antitumor activities are achieved by combination therapy with VEGF and HIF-1α-targeted agents. Our findings suggest that EBV creates plasticity in epithelial cells to express endothelial phenotype and provides a novel EBV-targeted antitumor strategy. EBV latent infection contributes to the pathogenesis of epithelial malignancies by inducing angiogenesis. Here, the authors show EBV promotes vasculogenic mimicry in EBV associated epithelial cancers via AKT/HIF-1α pathway and combination therapy of HIF-1α and VEGF reduces tumour growth.